2009
DOI: 10.1038/nchem.410
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective sulfonylation reactions mediated by a tetrapeptide catalyst

Abstract: While Nature excels at performing selective modifications of complex polyfunctional molecules through the use of tailoring enzymes, synthetic chemistry has lagged behind in this regard. In prior work, we have applied a biomimetic approach to this problem, developing small peptides to achieve various group transfer reactions on polyol substrates with high enantio- or regioselectivity. The utility of sulfonates as synthetic building blocks and the scarcity of direct, selective methods for their preparation promp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
58
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(59 citation statements)
references
References 29 publications
1
58
0
Order By: Relevance
“…Whereas small rigid organocatalysts offer only a limited number of sites for structural and functional diversity, peptides have a modular nature, which allows the creation of optimized catalysts. large number of peptidic catalysts have been designed [37], and it has been shown that N-terminal prolyl-peptides efficiently catalyze reactions proceeding via enamine intermediates [38]. Earlier, we reported the first continuous-flow approach for the selective asymmetric synthesis of -nitroaldehydes, utilizing solid supported peptidic catalysts readily synthesized and immobilized in a single step [39].…”
Section: Peptide Catalyzed Stereoselective Reactions In a Continuous-mentioning
confidence: 99%
“…Whereas small rigid organocatalysts offer only a limited number of sites for structural and functional diversity, peptides have a modular nature, which allows the creation of optimized catalysts. large number of peptidic catalysts have been designed [37], and it has been shown that N-terminal prolyl-peptides efficiently catalyze reactions proceeding via enamine intermediates [38]. Earlier, we reported the first continuous-flow approach for the selective asymmetric synthesis of -nitroaldehydes, utilizing solid supported peptidic catalysts readily synthesized and immobilized in a single step [39].…”
Section: Peptide Catalyzed Stereoselective Reactions In a Continuous-mentioning
confidence: 99%
“…[47] Site-specific or spatially controlled sulfonation reactions are known to be mediated by tailoring enzymelike peptide catalysts. [48] Organocatalysis involving photons for completing SET cycles allows some specificity in catalysis initiation by utilising particular wavelengths in the UV/ Vis range. [49] In combination with host-guest chemistry, binding interactions can be spatially configured to localise organocatalytic events for enhanced catalytic proficiency.…”
Section: Evolution Of Catalytic Proficiency and Complexity: Spatial Amentioning
confidence: 99%
“…46 This approach was also explored in reactions analogous to those catalyzed by kinases, culminating in the realization of peptide-catalyzed desymmetrizations of inositol derivatives (Figure 4C). 4751 Here, two distinct peptide scaffolds are utilized to access different phosphorylated derivatives of 8 . These early reports of peptide-based nucleophilic catalysis helped establish a basis for the application of these concepts to the more complex substrates that are described below.…”
Section: Group Transfer To Hydroxyl Groupsmentioning
confidence: 99%